2018
DOI: 10.3389/fmicb.2018.01563
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Ethanol and Temperature on the Fitness Advantage of Predominant Saccharomyces cerevisiae Strains Occurring in Spontaneous Wine Fermentations

Abstract: Different Saccharomyces cerevisiae strains are simultaneously or in succession involved in spontaneous wine fermentations. In general, few strains occur at percentages higher than 50% of the total yeast isolates (predominant strains), while a variable number of other strains are present at percentages much lower (secondary strains). Since S. cerevisiae strains participating in alcoholic fermentations may differently affect the chemical and sensory qualities of resulting wines, it is of great importance to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 75 publications
4
24
0
Order By: Relevance
“…However, considering the frequency of different S. cerevisiae strains within each winery in the various vintages, showed one or two predominant strains occurring at high frequencies (>25%), in association with a variable number of secondary strains at low frequencies (<10%), (Table 2). In addition, some predominant strains were shared by different grape varieties fermented in various tanks, pointing out that no correlation occurred between specific yeast strains and the grape variety, as reported by Ganucci et al [8]. The occurrence of a few predominant S. cerevisiae strains at percentages >25% carrying out the spontaneous wine fermentations, is consistent with many other studies accomplished in different oenological regions [6][7][8][11][12][13]19].…”
Section: The Biodiversity Of S Cerevisiae Isolates From Different Wisupporting
confidence: 88%
See 2 more Smart Citations
“…However, considering the frequency of different S. cerevisiae strains within each winery in the various vintages, showed one or two predominant strains occurring at high frequencies (>25%), in association with a variable number of secondary strains at low frequencies (<10%), (Table 2). In addition, some predominant strains were shared by different grape varieties fermented in various tanks, pointing out that no correlation occurred between specific yeast strains and the grape variety, as reported by Ganucci et al [8]. The occurrence of a few predominant S. cerevisiae strains at percentages >25% carrying out the spontaneous wine fermentations, is consistent with many other studies accomplished in different oenological regions [6][7][8][11][12][13]19].…”
Section: The Biodiversity Of S Cerevisiae Isolates From Different Wisupporting
confidence: 88%
“…The results shown in Table 2 revealed that, independently of the winery, indigenous S. cerevisiae populations showed a high amount of polymorphism, confirming the general trend reported in the literature on spontaneous wine fermentations [2][3][4][5][6][7][8][11][12][13][14][15][16][17][18][19]22,24]. However, considering the frequency of different S. cerevisiae strains within each winery in the various vintages, showed one or two predominant strains occurring at high frequencies (>25%), in association with a variable number of secondary strains at low frequencies (<10%), (Table 2).…”
Section: The Biodiversity Of S Cerevisiae Isolates From Different Wisupporting
confidence: 85%
See 1 more Smart Citation
“…Some winemakers argue that authentic expression of terroir and vintage can only be achieved through fermentation with indigenous yeasts. Other winemakers prefer the greater security and controlled variability of specialized strains [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, low temperatures also dramatically increase the time taken until fermentation completion and the risk of ferments becoming stuck or sluggish, which is potentially costly in terms of reduced winery space, product loss and decreased pro ts [4][5][6][7][8]. Low temperatures encountered during fermentation are particularly stressful to yeast and cause changes in cell membrane uidity, nutrient uptake and utilization, production of protective compounds, and a decrease in enzymatic reactions [6,[9][10][11]. A greater understanding of the genetics behind the ability of the wine yeast, Saccharomyces cerevisiae, to acclimate to low temperatures and perform fermentation more e ciently in general, is therefore useful for the wine industry.…”
Section: Introductionmentioning
confidence: 99%